2011
DOI: 10.1177/0145482x1110500309
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Rationale for using the Individualized Meaning-centered Approach to Braille Literacy Education with Students who have Mild to Moderate Cognitive Disabilities

Abstract: This article describes the components of the Individualized Meaning-centered Approach to Braille Literacy Education for teaching braille reading and writing to students who are blind and have additional cognitive impairments. A theoretical rationale is presented for the approach, along with some limited empirical evidence for using it with this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The foundation of approaching literacy from a functional standpoint is the use of words that are functional and meaningful to the student (Wormsley, 2004). Wormsley (2011) promotes a functional approach to braille literacy that teaches vocabulary words that "spark excitement, engagement, and emotion in students" (p. 147). If teachers select words that are engaging, students are more motivated to learn and use the words (Wormsley, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The foundation of approaching literacy from a functional standpoint is the use of words that are functional and meaningful to the student (Wormsley, 2004). Wormsley (2011) promotes a functional approach to braille literacy that teaches vocabulary words that "spark excitement, engagement, and emotion in students" (p. 147). If teachers select words that are engaging, students are more motivated to learn and use the words (Wormsley, 2004).…”
mentioning
confidence: 99%
“…If teachers select words that are engaging, students are more motivated to learn and use the words (Wormsley, 2004). Although Wormsley (2004;2011) provides a framework for teaching braille to students with intellectual disabilities and atrisk braille readers, specific, evidence-based teaching strategies to promote efficient reading of highly motivating words within the functional approach are needed.…”
mentioning
confidence: 99%
“…Wormsley (2011) developed an approach to braille reading instruction for children with mild cognitive disabilities called the Individualized Meaning-centered Approach to Braille Literacy Education (I-M-ABLE). This approach focuses on key vocabulary instruction using highly motivating words, phonics, contractions, and teaching efficient hand use.…”
Section: Braille Readingmentioning
confidence: 99%
“…Approximately 39% to 68% of students with uncorrectable VI have additional disabilities (Hatton, Ivy, & Boyer, 2013;Hatton, Schwietz, Boyer, & Rychwalski, 2007;Kong, Fry, Al-Samarraie, Gilbert, & Steinkuller, 2012). Research has shown that the presence of additional disabilities places students with VI at even greater risk for becoming nonreaders (Wormsley, 2011). Despite the apparent literacy gap between sighted peers and students with VI, literacy goals for students with VI should be comparable to those of their sighted peers.…”
Section: Introductionmentioning
confidence: 99%